From the AKAP to AKAIE model to assess the uptake of technological innovations in the aquaculture sector - Yari Vecchio; Margherita Masi; Felice Adinolfi (John wiley & Sons Australia, Ltd., 2025)
The purpose of this study is to explore the adoption of innovation in the aquaculture sector through the Awareness Knowledge Adoption Implementation Effectiveness (AKAIE) sequence. The AKAIE is an extension of the Awareness Knowledge Adoption Product (AKAP) model in order to better investigate the post-adoption phases. Using the ‘Implementation’ and ‘Effectiveness’ phases, this study aims to further the understanding of both the different levels of adoption and the impact of innovation in terms of environmental, economic and social benefits produced. The proposed sequence is contextualised in light of the multidimensional scenario of on-farm and off-farm factors acting alongside the adoption of new technologies in the aquaculture sector. In this paper, the perspective of aquaculturists is represented with the concept of perceived complexity as the central node of the adoption process. The proposed tool could support policy makers in understanding and disseminating innovation in aquaculture.